2021
DOI: 10.1002/jhbp.877
|View full text |Cite|
|
Sign up to set email alerts
|

Current status and management of pancreatic trauma with main pancreatic duct injury: A multicenter nationwide survey in Japan

Abstract: Background: Pancreatic trauma is reportedly associated with high morbidity and mortality. Main pancreatic duct (MPD) injury is critical for treatment. Methods: As a study project of the Japanese Society for Abdominal Emergency Medicine (JSAEM), we collected the data of 163 patients with pancreatic trauma who were diagnosed and treated at JSAEM board-certified hospitals from 2006 to 2016. Clinical backgrounds, diagnostic approaches, management strategies, and outcomes were evaluated. Results: Sixty-four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
2
10
0
4
Order By: Relevance
“…1 We concur that major pancreatic injuries still result in considerable morbidity, even when treated in well-resourced referral centers, and strongly endorse the notion proposed by the authors that experienced teams should be involved in the management of such injuries as in the JSAEM study. 1 We agree that it is judicious to involve a proficient pancreatic surgeon at an early stage as the technical intricacies both for resection and reconstruction of complex pancreatic injuries require special organ-specific surgical skills and expertise. 2 The authors do not detail the specifics, but current data support the use of initial damage-control laparotomy for complex combined pancreaticoduodenal injuries and delayed pancreatoduodenectomy (PD) once compromised patient physiology has been corrected.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…1 We concur that major pancreatic injuries still result in considerable morbidity, even when treated in well-resourced referral centers, and strongly endorse the notion proposed by the authors that experienced teams should be involved in the management of such injuries as in the JSAEM study. 1 We agree that it is judicious to involve a proficient pancreatic surgeon at an early stage as the technical intricacies both for resection and reconstruction of complex pancreatic injuries require special organ-specific surgical skills and expertise. 2 The authors do not detail the specifics, but current data support the use of initial damage-control laparotomy for complex combined pancreaticoduodenal injuries and delayed pancreatoduodenectomy (PD) once compromised patient physiology has been corrected.…”
supporting
confidence: 81%
“…
Dear Editor, We congratulate Drs Ando and Okano and colleagues from the Japanese Society for Abdominal Emergency Medicine (JSAEM) on their excellent analysis and the exceptional outcome of patients treated for main pancreatic duct (MPD) injuries. 1 We concur that major pancreatic injuries still result in considerable morbidity, even when treated in well-resourced referral centers, and strongly endorse the notion proposed by the authors that experienced teams should be involved in the management of such injuries as in the JSAEM study. 1 We agree that it is judicious to involve a proficient pancreatic surgeon at an early stage as the technical intricacies both for resection and reconstruction of complex pancreatic injuries require special organ-specific surgical skills and expertise.
…”
supporting
confidence: 81%
“…A recent multicenter national survey in Japan showed that serum amylase levels and ERCP can more accurately indicate injury to the main pancreatic duct in hemodynamically stable patients. Poor outcomes were reported in patients with long-standing injuries who were initially managed nonoperatively[ 13 ].…”
Section: Indications and Options For Surgical Managementmentioning
confidence: 99%
“…NOM strategies combined with internal and external drainage is thought to be bene cial in the acute and delayed phase by inducing less surgical stress, thereby lowering the in ammatory cascade, especially in already critically ill patients with serious injury [25,31,32]. This, considering the fact that pancreatic trauma is a complex and rare disease, makes it unlikely that a trial with a su ciently large sample size to study clinical outcomes will ever be performed [4,22,24,26,33,34]. It therefore remains unclear if NOM strategies improve prognosis, especially in the context of other recent changes in the treatment.…”
Section: Introductionmentioning
confidence: 99%